Evaluating the effectiveness of interactive M-learning in fostering EFL vocabulary for enhanced speaking proficiency - Khan, Raja Muhammad Ishtiaq; Alharbi, Majed Abdullah; Noor Raha, Mohd Radzuan (Bilingual Publishing Group, 2024)
This study aims to assess the impact of interactive vocabulary learning via WhatsApp on the speaking proficiency of English as a Foreign Language (EFL) learners in Saudi Arabia. Drawing on Krashen’s input Hypothesis and Cognitive Theories of Multimedia Learning, the research employs a quantitative approach involving sixty EFL learners from an English language foundation program. Two pre-formed elementary-level groups were randomly assigned as control and experimental groups. The findings indicate that the intervention group showed significant improvements in both vocabulary and speaking tests. To maximize WhatsApp’s effectiveness, it is recommended that content be dynamically designed to accommodate diverse learners, include both genders in future studies, and incorporate video clips and additional images to enhance vocabulary learning and speaking proficiency, with careful planning of vocabulary activities being crucial.